Metaevaluation in Practice - Leslie J. Cooksy; Valerie J. Caracelli (The Evaluation Center at Western Michigan University, 2009)
This paper examines the practice of metaevaluation as indicated by the Metaevaluation standard of the Program Evaluation Standards, as the evaluation of a specific evaluation to inform stakeholders about the evaluation's strengths and weaknesses. The findings from an analysis of eighteen metaevaluations, including a description of the data sources and methods used to come to conclusions about the evaluation and the criteria of quality employed, are reported. A diverse set of practices were identified, ranging from the use of emergent criteria in a narrative review of information about an evaluation to the structured application of the Program Evaluation Standards using a checklist. The paper concludes that the evaluation field does not have a common understanding of metaevaluation practice.